Root aquaporins contribute to whole plant water fluxes under drought stress in rice (Oryza sativa L.) - Grondin, Alexandre; Mauleon, Ramil; Vadez, Vincent; Henry, Amelia (Wiley, 2016)
Aquaporin activity and root anatomy may affect root hydraulic properties under drought stress. To better understand the function of aquaporins in rice root water fluxes under drought, we studied the root hydraulic conductivity (Lpr) and root sap exudation rate (Sr) in the presence or absence of an aquaporin inhibitor (azide) under well‐watered conditions and following drought stress in six diverse rice varieties. Varieties varied in Lpr and Sr under both conditions. The contribution of aquaporins to Lpr was generally high (up to 79% under well‐watered conditions and 85% under drought stress) and differentially regulated under drought. Aquaporin contribution to Sr increased in most varieties after drought, suggesting a crucial role for aquaporins in osmotic water fluxes during drought and recovery. Furthermore, root plasma membrane aquaporin (PIP) expression and root anatomical properties were correlated with hydraulic traits. Three chromosome regions highly correlated with hydraulic traits of the OryzaSNP panel were identified, but did not co‐locate with known aquaporins. These results therefore highlight the importance of aquaporins in the rice root radial water pathway, but emphasize the complex range of additional mechanisms related to root water fluxes and drought response.